The Differential Expression of EphB2 and EphB4 Receptor Kinases in Normal Bladder and in Transitional Cell Carcinoma of the Bladder - Li, Xiuqing; Choi, Wesley W.; Yan, Rui; Yu, Haiyang; Krasnoperov, Valery; Kumar, S. Ram; Schuckman, Anne; Klumpp, David J.; Pan, Chong-Xian; Quinn, David; Gill, Inderbir S.; Gill, Parkash S.; et al. (PloS one, 2014)
Effective treatment of transitional cell carcinoma (TCC) of the bladder requires early diagnosis. Identifying novel molecular markers in TCC would guide the development of diagnostic and therapeutic targets. Ephrins mediate signals via tyrosine kinase activity that modulates diverse physiologic and developmental processes, and ephrins are increasingly implicated in carcinogenesis. The aim of our study was to examine the differential regulation of EphB4 and EphB2 in normal bladder and in TCC of the bladder in 40 patients undergoing radical cystectomy for curative intent. Immunostaining and Western blotting revealed that normal urothelium expresses EphB2 (20 of 24 cases, 83% of the time) not EphB4 (0 of 24 cases, 0%). In sharp contrast, TCC specimens show loss of EphB2 expression (0 of 34 cases, 0%) and gain of EphB4 expression (32 of 34, 94%). Furthermore, EphB4 signal strength statistically correlated with higher tumor stage, and trended toward the presence of carcinoma in situ (CIS). These results are confirmed by analysis of normal urothelial and tumor cell lines. EphB2 is not a survival factor in normal urothelium, while EphB4 is a survival factor in TCC. Treatment of bladder tumor xenograft with an EphB4 inhibitor sEphB4-HSA leads to 62% tumor regression and complete remission when combined with Bevacizumab. Furthermore, tissue analysis revealed that sEphB4-HSA led to increased apoptosis, decreased proliferation, and reduced vessel density, implicating direct tumor cell targeting as well as anti-angiogenesis effect. In summary loss of EphB2 and gain of EphB4 expression represents an inflection point in the development, growth and possibly progression of TCC. Therapeutic compounds targeting EphB4 have potential for diagnosing and treating TCC.